2021
DOI: 10.2185/jrm.2021-022
|View full text |Cite
|
Sign up to set email alerts
|

Improving person-centered advance care planning conversation with older people: a qualitative study of core components perceived by healthcare professionals

Abstract: Objective: The non-medical needs of patients, such as values and personal preferences, are likely to be omitted from advance care planning (ACP) discussions because of a lack of readiness and awareness on the part of healthcare professionals. The aim of the present study was to identify core components perceived by multidisciplinary healthcare professionals to improve person-centered ACP conversations with older people. Methods: The study participants were healthcare professionals (physicians, nurses, and care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The wishes and needs of residents and close relatives were not included in the policy making and little attention was paid to their autonomy [ 42 ]. In a recent study, healthcare professionals reported that the highest value should be placed on the autonomy of older people to achieve successful person-centered care that respects their values [ 43 ]. The loss of autonomy and self-determination was also mentioned as contributing to loneliness [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The wishes and needs of residents and close relatives were not included in the policy making and little attention was paid to their autonomy [ 42 ]. In a recent study, healthcare professionals reported that the highest value should be placed on the autonomy of older people to achieve successful person-centered care that respects their values [ 43 ]. The loss of autonomy and self-determination was also mentioned as contributing to loneliness [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite widespread efforts to promote ACP, the actual completion rate is still low, partly owing to clinicians' lack of knowledge and awareness of ACP [8,9]. Also due to the absence of legislation specifically encouraging ACP in Japan, it is less practiced in this country than in the United States and the United Kingdom [8], where specific laws and policies on the issue have been adopted.…”
Section: Introductionmentioning
confidence: 99%